Contributions of single-particle cryoelectron microscopy toward fighting COVID-19. Issue 2 (February 2022) - Rapp, Micah; Shapiro, Lawrence; Frank, Joachim
Abstract : Single-particle cryoelectron microscopy (cryo-EM), whose full capabilities have been realized only within the past decade, has had a pivotal role in the fight against COVID-19. This is due to the technique's intrinsic power to depict both structural and dynamic features of molecules; in this case, of the spike protein of SARS-CoV-2. By now, numerous cryo-EM studies have furthered our understanding of spike protein–angiotensin-converting enzyme 2 (ACE2) receptor interactions, which has informed the design of effective vaccines, and have enabled the characterization of neutralizing antibody binding sites, which will lead to the design of novel therapeutics as the virus evolves. Highlights: The fight against the COVID-19 pandemic relies to a great extent on cutting-edge research in structural biology. Cryo-EM has made major contributions in elucidating structures of virus and host proteins. Cryo-EM has played a crucial role in the development of vaccines and antibodies.